Investigating Consumer Acceptability of Selected Amaranthus Genotypes in Mukono District - James Iranya Ekoku (Uganda Christain University, 2025)
Amaranthus, commonly referred to as African spinach, is an indigenous leafy vegetable recognized for its high nutritional value. Despite its potential contribution to food and nutritional security, consumer preferences for different Amaranthus genotypes in Mukono District, Uganda, remained largely unknown. In the gene bank of Uganda Christian University, there are over 14 genotypes of Amaranths. There is need to test for consumers acceptability for this genotypes, five were selected to enable breeding and development of variety that consumer would like. The breeder’s knowledge gap hinders efforts to identify consumer-preferred genotypes, which is essential for guiding breeding programs aimed at developing improved and widely accepted varieties. This study therefore investigated consumer acceptability of five Amaranthus genotypes (standard dodo, red dodo A025, local dodoA007, Grain dodo, and long leaf A008) in Mukono District, focusing on physical and sensory traits. Using a Consumer sensory acceptability as dependent variables traits like Color, Aroma, Taste, Mouth feel, Texture and General acceptability were considered and in Physical traits (Number of leaf, Leaf size, Leaf color, Leaf shininess, leaf shape, Leaf smoothness, Succulence, general acceptability, were considered. through consumer panels. Genotypes from Uganda Christian University's gene bank served as the independent variable, while consumer acceptability scores functioned as the dependent variable. the p-values were less than 0.001, this indicates that there is a significant difference in consumer’s preference base on the physical traits of the Amaranthus , while consumer sensory attributes of mouth feel and texture of p-value 003 and p-value = 028 indicates significant differences in the sensory evolution. This study concludes that breeders should focus on breeding standard dodo and local dodo A007 for commercial production basing on their likeness for physical traits and Red dodo A025 should be improved in the physical traits like size and leaf smoothness.